Beyond the kingdoms - Colfer, Chris, 1990-; Dorman, Brandon (New York : Little, Brown and Company, 2015)
The Masked Man possesses a powerful magic potion that turns every book it touches into a portal, and he is recruiting an army of literature's greatest villains! So begins a race through the magical Land of Oz, the fantastical world of Neverland, the madness of Wonderland, and beyond. Can twins Alex and Conner catch up to the Masked Man?
Sequel to: A Grimm warning.
5.3
3-6
760L
Keywords: Fairy tales -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Twins -- Juvenile fiction; Fairy tales -- Fiction; Characters in literature -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Twins -- Fiction